Journalistic-Based Scientific Writing Training Management Model for Madrasah Aliyah Teachers - Sihotang, Donald Harris; Patimah, Siti; Pahrudin, Agus; Rinaldi, Achi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
The purpose of this study was to find a good academic writing training management model for teachers of MAN 1 Bandar Lampung so that it can improve the professional competence of teachers. This study uses an approach with the ADDIE development model. The research subjects totaled 10 (ten) respondents in the preliminary study and 20 (twenty) people as training participants. Data collection used questionnaires, interviews, observation, and documentation. Then, the results were analyzed using an inductive method: data analysis, which proceeds from facts to theory. The results of this study were that training in writing journalistic-based scientific papers for teachers of MAN 1 Bandar Lampung was successful, and the skills of writing scientific papers based on journalism for teachers of MAN 1 Bandar Lampung could be improved. Based on these conclusions, a scientific writing journalism training management model was found with five stages: determining training needs, designing training, developing training designs, implementing the developed training designs, and evaluating training.